Bakti Sosial dengan Pembagian Sembako Kepada Masyarakat Miskin di Kota Surabaya - Rahayu Mardikaningsih; Ella Anastasya Sinambela; Didit Darmawan; Samsul Arifin; Arif Rachman Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Community service activities during the COVID-19 pandemic were aimed at underprivileged communities in areas affected by this event. This service activity was carried out to help the community in the Sidotopo Wetan Village, Surabaya City in terms of basic needs in order to survive the Covid-19 pandemic. Social service activities are a form of embodiment of caring attitudes, helping each other. Social service activities are a form of nabusia nature that has sympathy and empathy. Social service is an activity that reflects a sense of caring for people in need and a desire to help alleviate their needs. One of them is by sharing basic needs which is a branch of social service as a community service activity. With this activity, we can forge a relationship between each other so that it will build intimacy between the community and the entire academic community of Sunan Giri University. The target of this basic food distribution activity is considered to have been achieved to relieve the people affected by the Covid-19 and those who cannot afford it in the hope of alleviating the community's needs